2016
DOI: 10.1155/2016/8219543
|View full text |Cite
|
Sign up to set email alerts
|

Novel Association of WNK4 Gene, Ala589Ser Polymorphism in Essential Hypertension, and Type 2 Diabetes Mellitus in Malaysia

Abstract: With-no-lysine (K) Kinase-4 (WNK4) consisted of unique serine and threonine protein kinases, genetically associated with an autosomal dominant form of hypertension. Argumentative consequences have lately arisen on the association of specific single nucleotide polymorphisms of WNK4 gene and essential hypertension (EHT). The aim of this study was to determine the association of Ala589Ser polymorphism of WNK4 gene with essential hypertensive patients in Malaysia. WNK4 gene polymorphism was specified utilizing mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A cumulative genetic risk score consisting of 14 of the 38 SNPs is important for hypertension and increased propensity for systolic blood pressure and may contribute to hypertension in T2DM in this country 10 . Another study conducted in Malaysia involving 320 volunteers classified based on hypertension (163) and normotensive (157) conditions showed that TT genotype/T allele of the WNK4 gene resulted in a close relationship between hypertension and T2DM 11 . While genetic study remained limited in Indonesia, it is been documented that polymorphism of rs87148, especially CC genotype and C allele, and CAPN10 had a significant association with HbA1c level and increased T2DM vulnerability, respectively 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative genetic risk score consisting of 14 of the 38 SNPs is important for hypertension and increased propensity for systolic blood pressure and may contribute to hypertension in T2DM in this country 10 . Another study conducted in Malaysia involving 320 volunteers classified based on hypertension (163) and normotensive (157) conditions showed that TT genotype/T allele of the WNK4 gene resulted in a close relationship between hypertension and T2DM 11 . While genetic study remained limited in Indonesia, it is been documented that polymorphism of rs87148, especially CC genotype and C allele, and CAPN10 had a significant association with HbA1c level and increased T2DM vulnerability, respectively 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Malaysia involving 320 volunteers divided based on hypertension (163) and normotensive (157) groups. The TT genotype/T allele of the WNK4 gene resulted in a close relationship between hypertension and diabetes mellitus 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Except for WNK2, the other members of WNKs family have been reported to be associated with blood pressure or hypertension. A lot of blood pressure-associated polymorphisms of WNKs have been identified, including rs1468326 [ 96 ], rs765250 [ 97 ], rs880054 [ 98 , 99 ], rs956868 [ 98 ], and rs12828016 [ 98 , 99 ] of the WNK1 gene ( Figure 2 C and Supplementary Table S3); and p.Ala589Ser [ 100 ] of the WNK4 gene.…”
Section: Genetic Variants Of Ion Channels In the Kidneymentioning
confidence: 99%